The Impact of COVID-19 on Service Provision for Emergency Department Patients Post-Opioid Overdose: A Field Report. Issue 5 (16th September 2021) - Collins, Alexandra B.; Beaudoin, Francesca L.; Samuels, Elizabeth A.; Wightman, Rachel; Baird, Janette
Abstract : Background: To minimize the spread of COVID-19, health and ancillary care providers altered service delivery patterns. These changes included an increase in reliance on telemedicine modalities, a reduction in services or hours of operation, and prohibiting guests and nonessential personnel from healthcare settings. We describe a rapid environmental assessment with senior emergency department (ED) practitioners in Rhode Island to understand how COVID-related procedural changes impact the provision of post-overdose care in ED. Methods: Semi-structured interviews were conducted with 14 senior healthcare practitioners in EDs across Rhode Island from June to July 2020. Interviews were part of a larger, ongoing study examining the implementation and effectiveness of post-opioid overdose care in EDs and sought to understand how COVID-19 had impacted the provision of services for people who use drugs (PWUD). Results: COVID-related policy changes challenged the provision of services to PWUD in the ED, and extended challenges in connecting people with OUD to services in the community. Specifically, challenges included transitions to telehealth modalities, required COVID tests for treatment services, and gaps in community resources. Conclusions: This study underscores opportunities to improve the delivery of services amid overlapping public health crises for PWUD, including bolstering the use of telemedicine in EDs and across the care continuum.